The impact of the Pentagram strategy on developing the aesthetic taste of the students of the Department of Art Education (Journal of the College of Basic Education, 2024)
The research aims to identify: the impact of the strategy of the Pentagram in developing the aesthetic taste of the students of the Department of Art Education, and to verify this, the following hypothesis was formulated: There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group, which are taught according to the Pentagram strategy, and the mean scores of the students of the control group, which are taught according to the traditional method, in the measure of aesthetic taste The research community was determined by the students of the third stage / Department of Art Education - Morning Study / College of Basic Education at Al-Mustansiriya University. The researcher selected the study material that will be taught during the period of the experiment, which is six topics from the Design Techniques subject, formulated (60) behavioral goals, and prepared daily plans for teaching the two research groups. The researcher prepared a measure of aesthetic taste It consists of (30) paragraphs, and its apparent validity, stability, level of difficulty of its paragraphs, and the strength of distinguishing its paragraphs were confirmed, and the researcher made sure of the validity and stability of its paragraphs. The female officer who studied the same material according to the usual method, and the researcher reached a set of recommendations and proposals.